STRATEGI KOMUNIKASI DALAM MENINGATKAN WISATAWAN BENTENG KOTA DI KECAMATAN TEMPILANG - Gustin Gustin (MEDIOVA: Journal of Islamic Media Studies, 2021)
Tourism is currently a new phenomenon in the world of tourism, and will be developed in various countries. tourists are very important in the progress of a country or city. The method used is qualitative, data collected using primary and secondary data. The analysis uses qualitative data analysis. The results of the analysis conclude that the communication strategy for tourist destinations in the city fortress of the Tempilang district is carried out through several stages in accordance with the communication strategy such as determining the audience, composing messages, determining the desired method, and determining the use of mass media and printed media. Aida and SWOT analysts are needed to determine a communication strategy. To make it easier to introduce the city fort in Tempilang, AIDA communication strategy and SWOT analysis are used. With the AIDA communication strategy and a structured SWOT analysis, it makes it easier to convey a message and the goals and objectives to be achieved. There is a strategy to increase the awareness of residents to come to visit the Tempilang city fort.